Recurrent pancreatitis - surgical treatment by means of coldoid - jejunostomy (Allen’s operation) - Palma, Eduardo C; Zubiaurre, Leandro; Varela López, Julio (Cirugía del Uruguay, 2020)
Presented at session 1st October 1952